Saudi Women Writers : Sociopolitical and Literary Landscapes - Al Mutlaq, Basma A (Taylor & Francis, 2025)
Saudi Women Writers: Sociopolitical and Literary Landscapes details the achievements of Saudi women fiction writers from the 1960s up to the present day, many of whose works have yet to be published in English translation. This book explores how various Saudi women writers’ works reflect deep social, religious and political changes over several key phases: the secularism of the 1960s and 1970s; the 1980s religious revival, or saḥwa; the post-saḥwa period; and the era of globalization. Engaging with intersectional feminism, that studies women’s texts as a multifaceted space of identity, power and agency, with the capacity to critique, and possibly dismantle, traditional hierarchies, especially amidst evolving social, religious and political landscapes. By examining the works of Samira Khashugji, Qmasha al-Olayyan, Omima al-Khamis, Zaineb Hefny, Badriya al-Beshir, Raja al-Sanea, Saba al-Herz and Warda Abdul Malik, this book charts a fresh course in literary criticism, moving beyond restrictive and monolithic perspectives. Saudi Women Writers: Sociopolitical and Literary Landscapes is an important and unique text which will be of use to both students and scholars of Gender Studies, Literature, Middle Eastern Studies, and Politics. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.